Learning Disability Documentation in Higher Education: What Are Students Submitting?. (February 2014) - Sparks, Richard L.; Lovett, Benjamin J.
This study examined the supporting documentation submitted by students with learning disability (LD) diagnoses. The participants were 210 students who were enrolled in a college support program for students with disabilities at a private liberal arts college. Findings showed that although most students submitted a psychoeducational evaluation, fewer than half submitted a complete evaluation that included an IQ test and a complete achievement battery that contained full cluster or composite scores and reported standard scores. Public school evaluators had completed larger numbers of incomplete evaluations than private clinicians. Above 20% of the evaluations had been completed more than 3 to 5 years earlier, and 12% were more than 5 years old. The findings from this study extend conclusions from other investigations to specialized support programs for students with LD, suggesting that the quality of documentation for LD submitted to these programs is often poor.